If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-2(x+10)=44
We move all terms to the left:
5x-2(x+10)-(44)=0
We multiply parentheses
5x-2x-20-44=0
We add all the numbers together, and all the variables
3x-64=0
We move all terms containing x to the left, all other terms to the right
3x=64
x=64/3
x=21+1/3
| 780-x=6 | | Y^2-6y=72 | | 5b2+15b=0 | | 92=6x+7(-3-4) | | 3xxx=486 | | s/8=96 | | 12(m+4/9)-16=118 | | -16x^2+5x+40=29 | | 3/4m=-41/2 | | 3/5c=13 | | 3.25m=-19.5 | | 3x+2=11;=4 | | 1/128=25^x+1 | | 3/5x=12/10 | | 7/8z=6 | | 3m=36-6 | | 7*9-7=x | | 12x-3x+84=12x+36 | | x.1.5=9/4.5 | | 38=8+6j | | C+3c=2 | | 0=-16t^2+80t-29 | | 0=-16t^2-80t-29 | | -3(d-4)=-2d-2(8=+4d) | | 5x−2=−8 | | y/7+13=21 | | 4(c+3c)=2 | | x3+x6=11 | | 7x27=90 | | 52/5+v=71/2 | | y-2/30=4/15 | | 2x*3=5x-2/7 |